2022
DOI: 10.1093/jamiaopen/ooac064
|View full text |Cite
|
Sign up to set email alerts
|

Framework for integrating electronic patient-reported data in routine cancer care: an Oncology Intake Questionnaire

Abstract: Objective As part of ongoing implementation of electronic patient-reported outcome tools at the Dana-Farber Cancer Institute, here we describe the development of the electronic New Patient Intake Questionnaire. Materials and Methods The original New Patient Intake Questionnaire includes a review of symptoms, oncology history, family history, health behaviors, health and social status, health literacy and numeracy, which was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Moffitt patient portal usage and EPQ completion rates have been consistently high among NPs seen at Moffitt since 2014, averaging 81% and 79%, respectively, notably higher than rates historically reported by others, 7,24 although consistent with more recent portal usage that has increased with the expansion of telehealth following the COVID‐19 pandemic 25–28 . The Moffitt patient portal provides patients with access to several services relevant to clinical care (e.g., scheduling) and encourages advanced completion of clinically relevant patient forms such as the EPQ, which may contribute to high completion rates.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Moffitt patient portal usage and EPQ completion rates have been consistently high among NPs seen at Moffitt since 2014, averaging 81% and 79%, respectively, notably higher than rates historically reported by others, 7,24 although consistent with more recent portal usage that has increased with the expansion of telehealth following the COVID‐19 pandemic 25–28 . The Moffitt patient portal provides patients with access to several services relevant to clinical care (e.g., scheduling) and encourages advanced completion of clinically relevant patient forms such as the EPQ, which may contribute to high completion rates.…”
Section: Discussionmentioning
confidence: 62%
“… 25 , 26 , 27 , 28 The Moffitt patient portal provides patients with access to several services relevant to clinical care (e.g., scheduling) and encourages advanced completion of clinically relevant patient forms such as the EPQ, which may contribute to high completion rates. In addition, the availability of the EPQ via tablet in the clinic also serves to optimize completion rates, 7 particularly among patients accessing emergent care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such an option may, however, limit the efficacy of ePROs, as patients would not be able to use this tool to report symptoms in real time when they are off-site. 26 It may therefore be worth lending connected tablets to patients so that they can complete ePROs at home, as has been done in other studies, 15,27,28 especially because this improved the ePRO completion rate. 27 Another alternative could be to train nurses to help patients to complete ePROs at home, as another study observed that 63% of their patients age 80 years or older had needed assistance to complete remote ePRO assessments.…”
Section: Discussionmentioning
confidence: 99%
“…26 It may therefore be worth lending connected tablets to patients so that they can complete ePROs at home, as has been done in other studies, 15,27,28 especially because this improved the ePRO completion rate. 27 Another alternative could be to train nurses to help patients to complete ePROs at home, as another study observed that 63% of their patients age 80 years or older had needed assistance to complete remote ePRO assessments. 29 Yet again patients would not be able to complete ePROs whenever they would feel like they need to report symptoms, and this could hinder the benefit of this monitoring.…”
Section: Discussionmentioning
confidence: 99%